The Millennial Students’ and English Teachers’ Perceptions on the Challenges and Characteristics of an Effective Teacher in the Society 5.0 Era - Rahayu, Nanik Sri; Shofiya, Arina; Hamidah, Nuriyatul (STAI Miftahul Ula Nganjuk, 2024)
In the fast-evolving landscape of education, every student needs an ideal teacher to achieve better learning outcomes. However, the characteristics of an ideal English teacher may vary depending on the context and generation of students. As society transitions into the Society 5.0 era, with its rapid technological advancements, the expectations for English teachers are also changing. Teachers must understand the challenges they face and adapt to the evolving needs of millennial students. This study aims to investigate millennial students’ and English teachers’ perceptions of the challenges and characteristics of effective English teachers in the Society 5.0 era. The research adopts a survey approach, collecting data through questionnaires. The participants were English department students and their teachers from several Islamic universities in East Java. The results showed that both millennial students and teachers share similar perceptions on the challenges and characteristics of an effective English teacher in certain aspects, although there were differences in their perceptions regarding other aspects. The study highlights the alignment and differences in perceptions between millennial students and teachers, emphasizing the evolving characteristics and challenges that English teachers face in the Society 5.0 context. These insights can inform future teacher preparation and professional development to meet the dynamic needs of students in a technology-driven society.